Taxonomy of health IT and medication adherence. Issue 3 (September 2015) - Mrosek, Rafael; Dehling, Tobias; Sunyaev, Ali
Abstract: Background: Patients' failure to take medication as prescribed – poor medication adherence – is a well-known issue. Health information technology (IT) presents itself as a promising approach to tackle poor medication adherence. Objectives: To deepen the understanding of what features health IT offers and how these address poor medication adherence, we examine existing health IT targeting medication adherence. Methods: Building on extant literature, we follow a systematic approach for taxonomy development in information systems to build a taxonomy of health IT focusing on medication adherence. Results: Health IT offers various promising ways to address poor medication adherence. Overall, we map 16 different types of health IT offerings on 7 different dimensions. The principal results are that health IT focusing on medication adherence should be developed in a patient-centered way because medication adherence is predominantly a matter of the patient and that mobile technologies are a seminal driver for health IT offerings focusing on medication adherence. Finally, the taxonomy identifies the core impacts of health IT on medication adherence. Conclusion: The taxonomy establishes an overview of current health IT offerings targeting medication adherence, offers insights into untapped potential for health IT, and yields valuable insights for health policy and technology. Future efforts must, however, address how to continuously motivate patients and how to better integrate and combine health IT offerings to unfold the full potential of health IT for addressing poor medication adherence. Highlights: Development of a taxonomy for health IT focusing on medication adherence. Guidance for development and enhancement of health policy and technology. Mobile technologies are increasingly integrated into healthcare. Insights into untapped potential of health IT. Identification of the core impacts of health IT on medication adherence.